Chromosome-level genome assembly of Megachile sculpturalis Smith (Hymenoptera, Apoidea, Megachilidae) - Guang Yang; Qingsong Zhou; Juanjuan Yang; Guoai Chen; Zeqing Niu; Michael Orr; Rafael Rodrigues Ferrari; Yihan Zhang; Xiaoyu Shi; Rui Cheng; Chaodong Zhu; Arong Luo (Scientific Data)
Abstract Megachile sculpturalis Smith, 1853 native to East Asia, is an important solitary bee species that has invaded both Europe and the United States. This study provides the first chromosome-level genome assembly of M. sculpturalis using a combination of Nanopore long reads, Illumina short reads, and Hi-C data. The genome comprises 296.99 Mb distributed across 16 chromosomes. N50, L50 and BUSCO completeness reached 19.128 Mb, 7 scaffolds, and 96.7%, respectively. The genome contains 104 Mb repetitive elements (35.02% of the assembly size) and 11,446 predicted protein-coding genes. This chromosome-level genome will serve as an essential genomic resource for future research on Megachilidae.